O patriarcalismo conectado em rede: a superexposição e a objetivação da mulher no mundo virtual - Damitz, Caroline Vasconcelos (2018)
The present dissertation has the purpose of studying gender violence in cases of revenge pornography in the virtual environment. In this sense, online violence against women is the manifestation of a parasitic patriarchy that is ubiquitously established in the multicultural society. The research intends to discuss if revenge pornography, as gender violence, is a criminal-law claim. For this, by emphasizing the patriarchal system, it tries to explain how the signs naturalize conducts and construct subjectivities, evaluating the interrelations of the people in the maintenance of gender stereotypes. Thereafter, it points to the Internet as an information and communication tool in the multicultural society. Finally, it investigates whether online revenge pornography should be a demand for cultural or a criminal -law exchange, from a feminist perspective. For the proposed studies, the research has as its theoretical framework power and gender equality. The method to be used in the research is the deductive. In view of this, the research will have for its theoretical content the doctrinal contribution in books and articles in the different disciplines to be dealt with, for this purpose Brazilian criminal law and jurisprudence. As for the procedure method, it will be the monographic. As a tool for conducting the investigative process, documentary, bibliographic and data collection techniques are used, with support in international normative instruments and foreign and national legislation. Moreover, on one hand, if socially constructed norms have fixed a place for the sexuality of women associated with ideas of modesty, privacy and lack of the right to pleasure, then, in the face of it, it is considered necessary to promote gender and behavioral education in virtual space, so that, for cultural reasons, the idea of respect for the human being is promoted, independently of a gender attribution. On the other hand, in the case of gender violence, one can integrate legislative tools that promote a rupture with the symbolism that form this scenario of male domination. In this sense, criminal-law as a space of power to protect the revenge pornography recognizes the feminist agenda as a necessary and pertinent for legal provision.